2016
DOI: 10.3390/ijms17091409
|View full text |Cite
|
Sign up to set email alerts
|

The Profiling and Identification of the Absorbed Constituents and Metabolites of Guizhi Decoction in Rat Plasma and Urine by Rapid Resolution Liquid Chromatography Combined with Quadrupole-Time-of-Flight Mass Spectrometry

Abstract: Guizhi decoction (GZD), a well-known traditional Chinese medicine (TCM) prescription consisting of Ramulus Cinnamomi, Radix Paeoniae Alba, Radix Glycyrrhizae, Fructus Jujubae and Rhizoma Zingiberis Recens, is usually used for the treatment of common colds, influenza, and other pyretic conditions in the clinic. However, the absorbed ingredients and metabolic compounds of GZD have not been reported. In this paper, a method incorporating rapid resolution liquid chromatography (RRLC) with quadrupole-time-of-flight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…The saponins detected in the YXDJ capsule were mainly triterpenoid saponins, which were the bioactive ingredients of Radix Glycyrrhizae. For saponin-related metabolites, the biotransformation pathways included glycosylation and demethylation, which were consistent with previous publications (Huang et al, 2018;Xiang et al, 2016).…”
Section: Possible Metabolic Routes Of Typical Prototypessupporting
confidence: 89%
“…The saponins detected in the YXDJ capsule were mainly triterpenoid saponins, which were the bioactive ingredients of Radix Glycyrrhizae. For saponin-related metabolites, the biotransformation pathways included glycosylation and demethylation, which were consistent with previous publications (Huang et al, 2018;Xiang et al, 2016).…”
Section: Possible Metabolic Routes Of Typical Prototypessupporting
confidence: 89%
“…As for paeoni orin, ferulic acid and paeonol, these three indicative components exist in the multi-CMMs in the herbal formula of NJP, but their minimum limits in the corresponding CMM are not speci ed all, and their contents vary greatly [29][30][31][32][33][34][35][36][37][38]. Therefore, the second grade limit for the three markers in NJP was speci ed as 60% of their mean contents in three TCMRDs.…”
Section: Resultsmentioning
confidence: 99%
“…Modern pharmacology studies have shown that GZD has two-way regulation effects on sweat glands, body temperature, immune function, gastrointestinal motility, blood pressure, etc. [ 13 , 33 , 34 ]. It also has anti-inflammatory, antibacterial, antiviral, antiallergic, analgesic, hypoglycemic, and cardiovascular protection effects [ 13 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%